Droughts in the context of climate changes in Ukraine - Pysarenko , V. M.; Pysarenko , P. V.; Pysarenko, V. V.; Gorb , O. O.; Chaika, T. O. (Scientific Progress & Innovations, 2019)
The purpose of the article is to prove the necessity of introducing systemic and scientifically grounded measures for the adaptation of agrarian production to new climatic conditions in connection with the increasing drought recurrences. Methods of research. The following scientific methods were the methodological basis of the research: historical-dialectical, analysis and synthesis, theoretical search and abstract-logical, mathematical and statistical analysis based on the research results conducted on farm lands of the private enterprise "Agro-ecology". The research results. The theories of climate changes, which are connected with droughts – the influence of solar activity, cosmic factors, anthropogenic impact on nature, have been investigated. The expediency of developing adaptation measures in agricultural production technology, which will enable to reduce the negative influence of weather, and technological measures on accumulation, conservation and rational use of moisture, especially in conditions of drought, has been substantiated. The impact on moisture preservation, productivity and profitability of agrarian production of different farming systems (intensive, organic, no-till, strip-till, precision farming, bio-enzyme technology, biogenic farming) has been shown. It is proved that the research of moisture-conserving farming systems, one of which is organic farming, in the conditions of climate change is topical. The elements of scientific novelty. The peculiarities of agro-technical methods favoring the accumulation, conservation and rational use of soil moisture, under the conditions of different farming systems have been determined. Practical significance. The studies of snow cover height effect on moisture reserves in a meter layer of soil at organic farming system have been conducted and they have shown the significant role of snow retention. The expediency of regulating crop moisture supply with such agro-technological measures as creating gates for snow retention, using forest bands, introducing crop rotation, correct structuring of sown areas, minimal soil tillage, using organic fertilizers, mulching field surface has been disclosed.